2012
DOI: 10.1016/j.drugalcdep.2011.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two elementary school-based prevention interventions on being offered tobacco and the transition to smoking

Abstract: Aims This study sought to more precisely delineate the mechanisms by which two early elementary school-based, universal (i.e., applied to the entire population regardless of risk status) preventive interventions increased survival to first tobacco cigarette smoked. Specifically, we examined whether the interventions’ effect on survival to first use was via the reduction of offers to smoke and/or through preventing the transition from first offer to smoking. Methods A total of 678 urban first-graders were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
2
20
1
Order By: Relevance
“…Classroom and family-centered interventions were limited to 1 st grade and targeted early learning and aggression. Prior work has examined the impact of these interventions on other risk behaviors (Ialongo et al, 1999; Storr et al, 2002; Bradshaw et al, 2009; Wang et al, 2012). One publication examined onset of marijuana use between 6 th and 8 th grades and found no intervention effects (Furr-Holden et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Classroom and family-centered interventions were limited to 1 st grade and targeted early learning and aggression. Prior work has examined the impact of these interventions on other risk behaviors (Ialongo et al, 1999; Storr et al, 2002; Bradshaw et al, 2009; Wang et al, 2012). One publication examined onset of marijuana use between 6 th and 8 th grades and found no intervention effects (Furr-Holden et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…(For more information on intervention effects, see [23,24,36,55]). The initial sample of 678 children was representative of students entering first grade in one of nine Baltimore City public schools in the fall of 1993.…”
Section: Samplementioning
confidence: 99%
“…Here also the focus is on environmental conditions or circumstances, experimentally assigned at random so as to bring suspected confounding variables into balance – in lieu of a focus on individual-level differences that may never be understood with any completeness. In this context, it is important to note a just-published study suggesting early impact of a primary prevention program on the timing of the first chance to try tobacco, with no additional impact on the actual first tobacco smoking experience – i.e., impact via ‘exposure opportunity’ circumstances (Wang et al, 2012). …”
Section: Toward More Definitive Evidence On These Topicsmentioning
confidence: 99%
“…I think that a more fruitful line of investigation has been launched in prevention research experiments (Furr-Holden et al, 2004; Wang et al, 2012) when randomization has been used to study sequential drug outcomes. Furr-Holden et al (2004) worked from experimental evidence on prevention of tobacco smoking reported by Kellam and Anthony (1998), and completed a partial replication study.…”
Section: Toward More Definitive Evidence On These Topicsmentioning
confidence: 99%